The Effectiveness Of Music Therapy On Reducing Stress In Preparing Thesis In Nursing Students at Lambung Mangkurat University - Habibah, Siti; Rahmah, Mutia; Nasution, Tina Handayani (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Introduction : Students often encounter various obstacles in the process of writing scientific papers, which can lead to stress. One effort to reduce stress is through natural music therapy. Aim : The effectiveness of natural music therapy in reducing stress during thesis writing among Nursing Students at Lambung Mangkurat University. Metode : This study employed a quasi-experimental design, specifically using a One-Group Pre-Test and Post-Test approach. The population of this research consisted of Nursing students at Lambung Mangkurat University who were in the process of writing their thesis, enjoyed natural sound music, and had no trauma associated with natural sounds. Samples were selected using a simple random sampling technique. Data collection was conducted by administering the Perceived Stress Scale (PSS) questionnaire. Results : Data analysis showed a significance value of